080 Home mechanical ventilation (HMV) in primary muscle disease: a 12-year single centre cohort study. Issue 6 (27th May 2022) - Murphy, Patrick; Marino, Phillip; Howard, Leo; Ramsay, Michelle; Kaltsakas, George; Hart, Nick; Howard, Robin
Abstract : HMV support is required to manage ventilatory failure in different primary muscle disorders with varying patterns of respiratory muscle weakness and progression. We present a series of 232 patients with dystrophies who received HMV. The number of patients with the condition and the mean duration of support to death (n=75) or December 2019 was; Duchenne Muscular dystrophy – 113 patients (64 alive: 49 died) received HMV for 70m (1–240). Myotonic dystrophy – 42 patients (40:2) - 52m (1–185). Limb girdle – 36 patients (18:18) – 71m (4–130). Congenital – 14 (all alive) – 50m (6–101). Facioscapulohumeral – 9 (8:1) – 94m (46–209) Becker – 8 (3:5) – 40m (15–120) Ventilation was generally supported with a NIPPY 3+ device using pressure control mode with varying dependence and interfaces according to disease severity and patient preference. 57% patients had established respiratory failure, 9% underwent tracheostomy, 51% used cough assist devices and 31% underwent gastrostomy. This series indicates that prolonged survival is possible for patients with primary muscle disease who develop respiratory muscle weakness. The ventilation method, the level of home support and the need for adjuvant support over long periods may vary according to the wishes of the patient, the extent of generalized limb and bulbar weakness, and the pattern of progression. robinhoward@nhs.net